1994
DOI: 10.1159/000133702
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of aneuploidy using multicolor fluorescence in situ hybridization on human sperm

Abstract: Single color fluorescence in situ hybridization (FISH) has been utilized on sperm to estimate nondisjunction rates for chromosomes 1, 12, 15, 16, X and Y. Using single-color FISH, one cannot distinguish nonhybridization from nullisomy nor disomy from diploidy. In order to provide an internal control, a multicolor FISH strategy was employed. Satellite probes specific for 13 human chromosomes were used on multiple semen samples from two normal donors. Two or three probes were hybridized simultaneously and scored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
58
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 8 publications
16
58
4
Order By: Relevance
“…Several single-probe approaches have yielded variable results of disomy 1 in spermatozoa [for review, see (8)], possibly due to variable diploidy frequencies interfering with the interpretation of results. The frequency of disomy for chromosome 7 in our study (0.06%) is in the range of another study that showed 0.00 to 0.09% disomy 7 in two men (9).…”
Section: Discussionsupporting
confidence: 65%
“…Several single-probe approaches have yielded variable results of disomy 1 in spermatozoa [for review, see (8)], possibly due to variable diploidy frequencies interfering with the interpretation of results. The frequency of disomy for chromosome 7 in our study (0.06%) is in the range of another study that showed 0.00 to 0.09% disomy 7 in two men (9).…”
Section: Discussionsupporting
confidence: 65%
“…The disomy rate (0.39%) for chromosome 17 in this study is comparable to those (0.33% and 0.31%) by Han et al (1992) and by Guttenbach et aL (1994a), while higher than that (0.13%) in the report of Bischoff et al (1994) (Table 5). The disomy rate (0.33%) obtained for chromosome 18 is comparable to those (0.36% and 0.25%) by Guttenbach et al (1994b) and by Bischoff et aL (1994), while higher than that Williams et al (1993) and by Griffin et al (1995) (Table 5). On the contrary, the diploidy rate in this study is comparable to those of other investigators (Han et al, 1992;Williams et aL, 1993;Miharu et aL, i994) (Table 5).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the effects of age [8,[17][18][19][20] and tobacco consumption [21,22] on these can be studied. The incidence of aneuploidy for almost all chromosomes has been established in different fertile male groups [23][24][25][26][27]. However, the frequency of these aneuploidies has been found to vary considerably (reviewed by Spriggs and coworkers [26,27].…”
Section: Discussionmentioning
confidence: 99%